2019
DOI: 10.1507/endocrj.ej18-0543
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between computed tomography-assessed density, abdominal fat volume, and glucose metabolism after sleeve gastrectomy in Japanese patients with obesity

Abstract: In this study, we investigated the relationships between body weight (BW), computed tomography (CT)-assessed abdominal adipose tissue, and the glycemic metabolic profile in obese Japanese patients following laparoscopic sleeve gastrectomy (LSG). This study analyzed adipose tissue compartments using CT methods before and 1 year after LSG. Thirty obese patients were studied, and variables measured included visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), density of VAT (VAT-D), and density of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Moreover, loss of VAT post-surgery was associated with the changes in fasting glucose and HOMA-IR levels at 3 months post-surgery in the PCOS group and with the changes in TC at 12 months postsurgery in the control group. This finding was generally consistent with those from previous studies reporting that decreased VAT may contribute to the improvement of IR and lipid metabolism [18,33]. Further analyses were performed to explore the factors that may predict changes in body fat distribution in PCOS patients after LSG.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, loss of VAT post-surgery was associated with the changes in fasting glucose and HOMA-IR levels at 3 months post-surgery in the PCOS group and with the changes in TC at 12 months postsurgery in the control group. This finding was generally consistent with those from previous studies reporting that decreased VAT may contribute to the improvement of IR and lipid metabolism [18,33]. Further analyses were performed to explore the factors that may predict changes in body fat distribution in PCOS patients after LSG.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, pregnancy and fertility rates increased in PCOS patients with morbid obesity, after LSG surgery, with few maternal and neonatal complications [13,14]. It was reported that LSG was beneficial in the reduction of VAT mass in patients with obesity [15,16], which may help to reduce inflammatory adipokine secretion, decrease branched-chain amino acids levels, and improve IR [17,18]. However, limited data are available on the changes in body fat distribution (especially VAT) in PCOS patients with obesity after LSG surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, especially visceral fat accumulation, secreted visfatin, interleukin-6, tumor necrosis factor Q, etc., cause insulin resistance [43] , which is one of the main reasons for atherosclerosis. At present, CT and MRI scans are the best methods for accurately evaluating visceral fat [44] . Domestic and foreign research results show that [45,46] a signi cant correlation exists between abdominal visceral fat and arteriosclerosis via CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…4 Imaging myocardial functions by tissue Doppler (TD) echocardiography have disadvantages like angle dependence, limited spatial resolution, and one-dimensional deformation analysis. LSG is expected to affect many systems, especially the cardiovascular system, by decreasing body fat deposition to different degrees.…”
mentioning
confidence: 99%
“…LSG is expected to affect many systems, especially the cardiovascular system, by decreasing body fat deposition to different degrees. 4 Imaging myocardial functions by tissue Doppler (TD) echocardiography have disadvantages like angle dependence, limited spatial resolution, and one-dimensional deformation analysis. Recently, these limitations were overcome through advances in two-dimensional speckle tracking echocardiography (STE) and the superiority of STE over Doppler strain was established.…”
mentioning
confidence: 99%